134k views
5 votes
Simplify -3[5 - (-8 + 6)]

User Amauris
by
5.0k points

2 Answers

3 votes

Answer:

-21

#RoadToGraduation

Explanation:

User Learnr
by
5.5k points
3 votes

First, solve the parenthesis

-8 + 6 = -2

-3[5 - (-2)]

Note that two negatives = one positive

-3[5 - (-2)] = -3[5 + 2]

Simplify. Solve the bracket

-3[5 + 2] = -3[8]

Simplify. Multiply to get the answer

-3 x 8 = -24

-24 is your answer

hope this helps

User Paul Syfrett
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.